Evaluation of the Triage Micro Parasite Panel for Detection of Giardia lamblia, Entamoeba histolytica/Entamoeba dispar, and Cryptosporidium parvum in Patient Stool Specimens - Sharp, Susan E. (American Society for Microbiology, 2001)
A study comparing the Triage Micro Parasite Panel (Biosite Diagnostics, Inc., San Diego, Calif.) to conventional O&P examination (O&P) was performed using patient fecal specimens. Five hundred twenty-three stool samples were compared. Nineteen specimens were found to be positive by Triage, and 29 were found to be positive by O&P. Seven specimens were positive for Giardia lamblia, four were positive for Entamoeba histolytica/E. dispar, and three were positive for Cryptosporidium parvum as determined by both methods. There was one false positive by Triage (C. parvum) and four false negatives by O&P (two G. lamblia, one E. histolytica/E. dispar, and one C. parvum). The Triage test accurately detected all 18 specimens that contained one of the three organisms that it was designed to detect. The Triage test is a rapid, easy-to-use enzyme immunoassay for the detection of G. lamblia, E. histolytica/E. dispar, and C. parvum in fresh or fresh-frozen fecal specimens. These data suggest that the Triage test can be used as a screen for the immediate testing of stool specimens for these three pathogenic parasites. If Triage test results are negative, O&P can be performed if parasitic infections other than G. lamblia, E. histolytica/E. dispar, or C. parvum are suspected.